Experimental research on the formation of future ship engineers' communicative competence based on gamification approach (Educational Dimension, 2020)
The articles is devoted to the experimental research on the of English-language communicative competence formation of future ship engineers. The method of usage of gamification approach to form the communicative competence is proposed. The model of English-language communicative competence formation based on gamification which includes target, normative, methodological, procedural, substantive and evaluative-effective blocks is described. The article also shows the experimental research results which confirm the effectiveness of the developed structural model of English-speaking competence of future ship engineers and the methods of its formation.